Cultivating Futures: Anthropological Explorations of Alternative Education in Indonesia - Annisa Sabrina Hartoto; Molly Fitzpatrick (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
Education has long been central to state-building projects and the formation of moral citizens worldwide, including in Indonesia. Yet, as social, political, and ecological crises intensify, new pedagogical experiments have emerged outside formal schooling—initiatives and movements that seek to cultivate alternative ways of knowing, learning, and living together. These spaces, often modest in scale but rich in imagination, challenge dominant educational paradigms oriented towards discipline, productivity, and national development. They illuminate how learning extends beyond the classrooms into everyday practices of care, critique, and community- building. This Special Issue examines these emerging forms of learning and sociality, tracing how they generate new political, moral, and affective possibilities for the future.